Effects of Serum Albumin Levels on Antithrombin Supplementation Outcomes Among Patients With Sepsis-Associated Coagulopathy: A Retrospective Study. Issue 12 (June 2019) - Ebina, Masatomo; Fujino, Kazunori; Inoue, Akira; Ariyoshi, Koichi; Eguchi, Yutaka
Background: Severe sepsis is commonly associated with mortality among critically ill patients and is known to cause coagulopathy. While antithrombin is an anticoagulant used in this setting, serum albumin levels are known to influence serum antithrombin levels. Therefore, this study aimed to evaluate the outcomes of antithrombin supplementation in patients with sepsis-associated coagulopathy, as well as the relationship between serum albumin levels and the effects of antithrombin supplementation. Methods: This retrospective study evaluated patients who were >18 years of age and had been admitted to either of two intensive care units for sepsis-associated coagulopathy. The groups that did and did not receive antithrombin supplementation were compared for outcomes up to 1 year after admission. Subgroup analyses were performed for patients with serum albumin levels of <2.5 g/dL or ⩾2.5 g/dL. Results: Fifty-one patients received antithrombin supplementation and 163 patients did not. The Cox proportional hazards model revealed that antithrombin supplementation was independently associated with 28-day survival (hazard ratio [HR]: 0.374, P = 0.025) but not with 1 year survival (HR: 0.915, P = 0.752). In addition, among patients with serum albumin levels of <2.5 g/dL, antithrombin supplementation was associated with a significantly lower 28-day mortality rate (9.4% vs 36.8%, P = .009). Conclusion: Antithrombin supplementation may improve short-term survival, but not long-term survival, among patients with sepsis-associated coagulopathy.